An attestation of the spatiality and saliency of police culture: a cross comparison study of croatian and cypriot novice law enforcers. (2nd January 2019) - Constantinou, Angelo G; Butorac, Ksenija
ABSTRACT: It is often maintained that factors such as the multifarious and exigent nature of the police profession, the diversity of police personnel, and the dissimilar socioeconomic and political settings which surround the sphere of policing, fragment the shared values, beliefs, and norms of police officers. As a result, the spatiality and saliency of such values (police culture), is doubted, if not denied. Such being the case, the article sets out to examine whether or not police culture, as documented to exist in Anglo-American police organisations, is reflected in two disparate settings, namely the Croatian and Cyprus Police. For attesting the foregoing, quantitative research was undertaken in these two settings. Upon analysing the responses of novice law enforcers (n = 185), it was found that the core constituents of police culture (isolation, suspicion, brotherhood, and cynicism), besides cynicism – which was partially supported – manifested in both police organisations.